Trajectories of prolonged grief one to six years after a natural disaster - Josefin Sveen; Kerstin Bergh Johannesson; Martin Cernvall; Filip K. Arnberg (2018)
Background The long-term trajectories of prolonged grief are poorly understood. The aims were to examine the course of grief among bereaved disaster survivors up to six years post loss and factors predicting worse bereavement outcome. A third aim was to explore differences in grief indicators between trajectories. Methods Bereaved Swedish tourists who survived the 2004 Indian Ocean tsunamis responded to surveys including the Inventory of Complicated Grief 1 to 6 years after the disaster. Latent growth mixture modeling was used to identify longitudinal trajectories of grief. Multinomial logistic regression analysis was used to examine predictors of class membership. Results Three trajectories were identified: resilient (41% of the sample), recovering (48%), and chronic (11%). The strongest predictor of chronic grief was the loss of one's child. When examining grief indicators, the chronic trajectory was characterized by not accepting the loss, while yearning was common in all trajectories. Conclusions This study highlights the importance of considering how traumatically bereaved individuals can be affected by loss for several years after a disaster, especially after losing one's child. An inability to accept the loss, more so than yearning, appears to characterize bereaved survivors at risk of a chronic trajectory of grief.